2021
DOI: 10.1186/s12874-020-01197-3
|View full text |Cite
|
Sign up to set email alerts
|

Methodology in core outcome set (COS) development: the impact of patient interviews and using a 5-point versus a 9-point Delphi rating scale on core outcome selection in a COS development study

Abstract: Background As the development of core outcome sets (COS) increases, guidance for developing and reporting high-quality COS continues to evolve; however, a number of methodological uncertainties still remain. The objectives of this study were: (1) to explore the impact of including patient interviews in developing a COS, (2) to examine the impact of using a 5-point versus a 9-point rating scale during Delphi consensus methods on outcome selection and (3) to inform and contribute to COS developme… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…There is currently no consensus on which rating scale should be used in COS development and, as such, different scales have been used in previous COS. The results of the embedded methodological study are reported elsewhere [24]. During the Delphi study, however, any outcome rated as important on either scale (Table 2), as per our consensus definition detailed below, was forwarded to the subsequent round.…”
Section: Plos Onementioning
confidence: 99%
“…There is currently no consensus on which rating scale should be used in COS development and, as such, different scales have been used in previous COS. The results of the embedded methodological study are reported elsewhere [24]. During the Delphi study, however, any outcome rated as important on either scale (Table 2), as per our consensus definition detailed below, was forwarded to the subsequent round.…”
Section: Plos Onementioning
confidence: 99%
“…Each item was graded from 1 to 9 ( De Meyer et al , 2019 ), with the additional option “I can’t rate the outcome because I don’t know the outcome”. Written anchors were provided to reduce measurement error ( Beckstead, 2014 ; Remus et al , 2021 ) (1. Extremely unimportant; 2.…”
Section: Methodsmentioning
confidence: 99%
“…In the third section, participants will be presented with statements and be invited to rate the importance of the implementation strategies. Whilst there is no gold standard for selecting an appropriate scale for consensus processes to identify implementation strategies [ 55 ], 9-point scales have been recommended by the Grading of Recommendations Assessment, Development and Evaluation (GRADE) Working Group to assess the importance of research evidence [ 56 ] and have been suggested to have more discriminatory power than other scales [ 57 ]. As such, a 9-point Likert scale will be used.…”
Section: Methodsmentioning
confidence: 99%